The effect of an Olympic distance triathlon on pulmonary diffusing capacity and its recovery 24 hours later - Boussana, A.; Galy, O.; Le Gallais, D.; Hue, O. (Journal of Human Kinetics, 2021)
The Olympic distance triathlon includes maximal exercise bouts with transitions between the activities. This study investigated the effect of an Olympic distance triathlon (1.5-km swim, 40-km bike, 10-km run) on pulmonary diffusion capacity (DLCO ). In nine male triathletes (age: 24 ± 4.7 years), we measured DLCO and calculated the DLCO to alveolar volume ratio (DL CO /VA) and performed spirometry testing before a triathlon (pre-T), 2 hours after the race (post-T), and the day following the race (post-T-24 h). DLCO was measured using the 9-s breath-holding method. We found that (1) DL CO decreased significantly between pre- and post-T values (38.52 ± 5.44 vs. 35.92 ± 6.63 ml·min - 1·mmHg -1) (p < 0.01) and returned to baseline at post-T-24 h (38.52 ± 5.44 vs. 37.24 ± 6.76 ml·min-1·mmHg-1, p > 0.05); (2) DL CO /VA was similar at the pre-, post- and post-T-24 h DLCO comparisons; and (3) forced expiratory volume in the first second (FEV 1) and mean forced expiratory flow during the middle half of vital capacity (FEF25-75%) significantly decreased between pre- and post-T and between pre- and post-T-24-h (p < 0.02). In conclusion, a significant reduction in DL CO and DL CO /VA 2 hours after the triathlon suggests the presence of pulmonary interstitial oedema. Both values returned to baseline 24 hours after the race, which reflects possible mild and transient pulmonary oedema with minimal physiological significance.